Crossover interference in the mouse. - Broman, Karl W (2002)
We present an analysis of crossover interference in the mouse genome, on the basis of high-density genotype data from two reciprocal interspecific backcrosses, comprising 188 meioses. Overwhelming evidence was found for strong positive crossover interference with average strength greater than that implied by the Carter-Falconer map function. There was some evidence for interchromosomal variation in the level of interference, with smaller chromosomes exhibiting stronger interference. We further compared the observed numbers of crossovers to previous cytological observations on the numbers of chiasmata and evaluated evidence for the obligate chiasma hypothesis.